A call for a community-driven participatory approach in restoring the heritage in the city of Chandannagar, West Bengal. Issue 1 (2nd January 2023) - Bose, Lina
ABSTRACT: Heritage always calls for inclusion, but when it comes to development, the inclusionary aspect of heritage is frequently undermined. In the contemporary era, the holistic heritage approach has frequently degraded into layers of ignorance and low-priority subjects. The neoliberal developmental paradigm alienated the community from their aesthetic and cultural values and forced them to move forward into a new era of development. This write-up encourages the community to participate in restoring the heritage elements in the city of Chandannagar by spreading the message 'conserve and feel proud.'. The field report looks for ways to integrate utilitarian developmental perspectives with non-utilitarian cultural values and praxis in Chandannagar.